Ocular Biometry among primary angle closure - Sherpa, Dakki (Journal of Chitwan Medical College, 2018)
Objective: To determine ocular biometry of primary angle closure. Materials and methods: A cross-sectional comparative study was carried out in Nepal Eye Hospital including thirty-six eyes of 29 diagnosed cases of primary angle closure and 44 eyes of 22 normal subjects selected by convenience sampling technique. A complete ocular examination of all the subjects was carried out. AL, ACD and LD measurement was done using ultrasound A scan. Result: Out of 80 eyes, there were 36 eyes of 29 diagnosed primary angle closure subjects and 44 eyes of 22 normal subjects. The mean age of primary angle closure patients were 61. 65+/- 10.44. The mean AL of PAC was 22.15mm +/-0.76. The mean AL of control group was 22.98 mm with SD of 0.63. The mean ACD of PAC patients were 2.85mm and SD of 0.46 and the mean ACD of control group was 3.59 with SD of .40. The mean lens diameter of PAC group was 4.57 mm +/- 0.58 and the mean LD of control group was 4.43mm +/- 0.54. The Sig (2-tailed) test showed: Age: 0.268, AL: 0.001, ACD: 0.000 and LD: 0.466. Conclusion: This study reveals that short AL and shallow ACD is a strong risk factor of primary angle closure. Though LD more than 4.5 mm is a risk factor of primary angle closure it is not statistically significant.